(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2026)
High fermentation temperatures will remain a major limitation to competitive bioethanol production in tropical countries and regions. The objective of the present study was to enrich indigenous microbial strains, improve their performance through Adaptive Laboratory Evolution (ALE), and identify a promising candidate for sustainable bioethanol production. A design an exploratory-comparative laboratory study design was used. Four isolates, Candida tropicalis (CT-BKL01), Kluyveromyces marxianus (KM-BKL02), Bacillus coagulans (BC-BKL03), and Zymobacter palmae (ZP-BKL04), were isolated, characterised, and evolved at elevated temperatures (up to 60 generations). Statistical methods included t-tests (paired and unpaired), fold-change values from proteomics, and nonlinear regression using the Monod-Haldane model. ALE results showed ALE significantly increased the specific growth rate, the activity of the enzyme (p < 0.05), and promoted overexpression of HSP70, GroEL, and ADH-II, whereas its improvement in ethanol titer was observed at 45 °C, with BC-BKL03 as the best strain exhibiting μmax of 0.63 h-¹ that had strong model-appropriate fits (R² ≥ 0.98). From a scientific point of view, this study offers an excellent non-recombinant approach for strain improvement without genetic modification. Operationally, this work contributes to SDGs 7 (Affordable and Clean Energy) and SDGs 13 (Climate Action) by enabling efficient production without active cooling. It enables regional energy sovereignty and reduces carbon emissions, offering a scalable solution for the renewable energy industry in tropical countries.